Drivers of HIV self-testing among female sex workers: Findings from a multi-state study in Malaysia - Kim, Rayne S.; Wickersham, Jeffrey A.; Maviglia, Francesca; Galka, Jonathan M.; Azwa, Iskandar; Gautam, Kamal; Shrestha, Roman (Frontiers in Medicine, 2023)
Background Although research on HIV self-testing (HIVST) has rapidly increased, few studies have explored HIVST uptake in female sex workers (FSW), and none in Malaysia. Therefore, we endeavored to assess the willingness to use HIVST in this at-risk, vulnerable population. Methods A cross-sectional survey study was conducted among 113 HIV-negative Malaysian FSW in 2017. Participants were recruited using advertisements on social media, flyers, and direct referrals from community-based organizations. Data were collected using self-administered surveys. Multivariable logistic regression was used to identify correlates of willingness to use HIVST. Results Nearly a third of participants (30.1%) reported they would be willing to use HIVST. Multivariable analyses adjusting for Malay ethnicity, stable housing, living in Kuala Lumpur (KL), years in sex work, age of first sex work, childhood sexual assault, history of HIV testing, and previously in prison indicated that living in KL [adjusted odds ratio (aOR) = 5.214, p = 0.0137] was associated with a greater willingness to use HIVST. In contrast, having stable housing (aOR = 0.100, p = 0.0064) was negatively associated with willingness to use HIVST. Conclusions Our results indicate that HIVST may potentially enhance the uptake of HIV testing among FSWs living in an urban environment and experiencing unstable housing, but an overall willingness to use HIVST is low. These findings highlight the need for efforts to increase awareness of HIVST among FSWs and additional research on the effective implementation of HIVST for FSW.